(untitled) (Asian Journal of Social Science Studies, 2018)
Educational exchange between Malaysia and China has an important interaction with the Chinese education in Malaysia and the political relations between Malaysia and China. Chinese education in Malaysia is twisted with Malaysian ethnic politics. Malaysian Chinese students were lack of opportunities at the public institutions of higher learning due to the preferential and affirmative action policies implemented by Malaysian government under the egis of New Economic Policy (NEP).Thus, Malaysia NGOs (Non-Governmental Organizations) carried out educational exchange with China to open up a more spacious study channels for students. The objective of this article is to investigate the role of Malaysian NGOs towards educational exchange between Malaysia and China under Malaysian ethnic politics. Primary data were collected through interviews and the informants were selected based on purposive sampling and snowball sampling. Totally, fourteen informants were selected and interviewed based on evidence of data saturation. Secondary data were collected from journal articles, newspapers, website pages and online resources. Meanwhile, structuration theory was used to guide the researcher to get the suitable answer. Findings of this study indicate that, there are three main important NGOs that play a significant role in promoting educational exchange between Malaysia and China, which are Dong Jiao Zong (the collective name of Dong Zong and Jiao Zong), the Association of Graduates from Universities and Colleges in China, Malaysia (AGUCCM) and Malaysia-China Friendship Association (MCFA). As the purposive actors, they conduct their actions based on different levels, which are to develop Chinese education in Malaysia, to continue and inherit Chinese culture. Their unconsciousness reason is based on Malaysian Chinese’s deep feeling to China. Moreover, the educational exchange in the aspect of Chinese education is conducted under the structure of Malaysian ethnic politics, which led to a dichotomy. Nowadays, with the rise of China and the promotion of “the Belt and Road”, educational exchange between Malaysia and China will become better and better.